Urinothorax Caused by Xanthogranulomatous Pyelonephritis - Waiel Abusnina; Hazim Bukamur; Zeynep Koc; Fauzi Najar; Nancy Munn; Fuad Zeid (Case Reports in Pulmonology)
Xanthogranulomatous pyelonephritis is a rare form of chronic pyelonephritis that generally afflicts middle-aged women with a history of recurrent urinary tract infections. Its pathogenesis generally involves calculus obstructive uropathy and its histopathology is characterized by replacement of the renal parenchyma with lipid filled macrophages. This often manifests as an enlarged, nonfunctioning kidney that may be complicated by abscess or fistula. This case details the first reported case of xanthogranulomatous pyelonephritis complicated by urinothorax, which resolved on follow-up chest X-ray after robot-assisted nephrectomy.